A Group Tasks Scheduling Algorithm for Cloud Computing Networks based on QoS - K. Jairam Naik, Dr.; Veda Vidhya, B. (International Journal of Engineering and Technology, 2018)
This article introduces a Novel Group-Tasks Scheduling Algorithm (NGTSA) which is used for allocating the tasks in the network of cloud computing by means of pertaining quality of services to gratify user’s desires. The tasks are categorized into five classes by the anticipated algorithm. Every one group contains the tasks with akin attributes (like, types of the users and tasks, size and latency of the task). Once the tasks are allocated to a precise group, scheduler starts assigning these tasks to accessible services. This assignment of tasks was performed in two steps: In Step-I is to decide which group tasks is to be scheduled foremost. Such decision will be based on the attributes of the tasks of each group. Hence, the groups which have higher task’s attribute values are scheduled foremost. Step-II is for taking internal decision that is which task from the selected group is scheduled foremost. This decision will be based on time needed for task’s execution. Therefore, the task which has the lowest time for execution will schedule foremost.
Keywords: Cloud Computing; Task Scheduling; Latency; Load Balancing; Services; Execution Time.